Pengembangan UKM Online Bagi Para Pengrajin Kapal Kayu di Kelurahan Tanah Lemo, Kecamatan Bontoharu, Kabupaten Bulukumba - hasna hasan (Faculty of Engineering UNHAS, 2020)
People in Kelurahan Tanah Lemo, Kecamatan. Bontoharu, Kabupaten Bulukumba, is phinisi ship craftman which has sold phinisi for years. However, phinisi business is not sucsessfull due to its traditional marketing system. Often, these craftman needs help from the third party in order to find buyers. So, they do not get high profit, eventhough the build process is heavy. However, this phinisi is potential to be exported, due to UNESCO acknowledgment about phinisi as a beautifull art creation. Procedure that is used in this program, consist of : - collecting and analysis data by interviewing the phinisi owner and observe the process of ship building. - website format design and develope. The output of the subjects; consist of : - process of ship building. - obstacles in phinisi business. - potency of phinisi business. In addition, output of analysis those data, which are : - define the aim of website which is to be the bridge for producer and consumer. - summaries some important point that need to be shown in this website. The analysis result become a reference in design the website which is consist of : - showing phinisi as an art creation as well as its capability in sailing around the world. - eventhough this website only for UKM, but still need to express its credibility. Therefore, the website is build using hand coding technique so its flexible and easy to modify. The target which is expected is introducing phinisi in overseas and increasing its marketing. So, this business impact on the increaseness of prosperity and a new vocation. In conclusion, due to the society high interest to phinisi, digitization of marketing system for phinisi is conducted using a website. This website is expected become a bridge for phinisi business and their buyers around the world.